Fault‐tolerant control design using the linear parameter varying approach. (24th May 2014) - Montes de Oca, Saúl; Tornil‐Sin, Sebastian; Puig, Vicenç; Theilliol, Didier; Edwards, Christopher; Marcos, Andres; Balas, Gary
SUMMARY In this paper, a fault‐tolerant control (FTC) design method based on linear parameter varying (LPV) gain‐scheduling theory is proposed. The main contribution is the design of a fault‐tolerant state‐feedback observer‐based controller based on a polytopic LPV representation where faults are considered in the same way that those parameters that vary with the operating point. Within this framework, the ranges of fault magnitudes that are wanted to be tolerated can be specified as design parameters. Control specifications are defined in terms of H ∞ or H2 performance in combination with regional pole placement, as traditionally carried out in conventional LPV control. Passive and active FTC formulations are developed, the latter assuming the availability of online fault estimations. In both cases, the associated controller synthesis methods are based on the well‐established LPV‐LMI framework. Additionally, a fault estimation procedure is provided to allow the implementation of the active formulation. Finally, the use of the proposed method is illustrated by applying it to the FTC of a two‐degree‐of‐freedom helicopter. Copyright © 2014 John Wiley & Sons, Ltd.